AB0714 Improvement of Refractory Dysphagia in Patients with Idiopathic Inflammatory Myopathies Receveing Immunoglobulin Intravenous Therapy. (9th June 2015) - Giannini, M.; Fiorella, M.L.; Coladonato, L.; D'Abbicco, D.; Amati, A.; Lopalco, G.; Laselva, G.; Lapadula, G.; Iannone, F.
Abstract : Background: Polymyositis (PM) and Dermatomyositis (DM) are systemic inflammatory diseases affecting skeletal muscles and other organs, particularly hypopharynx and the upper tract of the esophagus, resulting in motility disfunction. The current treatment for PM and DM consists of steroids and immunosuppressants, but esophageal involvement is often refractory to standard therapies. Objectives: To assess the efficacy and safety of intravenous immunoglobulins (Ig-iv) as therapy of refractory dysphagia in patients affected by idiopathic inflammatory myopathies (IIM) who have received conventional treatments for at least three months. Methods: We enrolled 11 patients (9 F), 4 with DM, 7 with PM according to Bohan and Peter criteria. At baseline, all patients had received prednisone (5-10 mg/day) associated to Methotrexate (15 mg/wk) or Azathioprine (100 mg/day) for at least 3 months, without improvement of dysphagia. All patients received Ig-iv at a standard dose (2 g/kg/day only for a day). In all patients at entry and after each infusion VES 1h, PCR, LDH, CK levels were measured and Manual Muscle Strength Test (MMT12 e MMT-tight) was made. Dysphagia assessment included: Eating Assessment Tool (EAT; positive for score ≥3), Three-oz Swallow Test (3oST) and fibrolaryngoscopy (FEES –pharyngeal muscle propulsion, stasis of liquid and solid bolus). For the statistical analysis we used Wilcoxon Rank test, Fisher Exact Test, Chi-square test. Results: At entry, there was evidence of correlation between MMT-12 and MMT-tight (p=0, 005); CK and LDH levels were increased and EAT score was ≥3 in all patients. After the Ig-iv therapy we observed a statistically significant decrease in LDH levels (p=0, 024), mainly between T0 and T1 (p<0, 05); there was also a downward trend in CPK levels (p=0, 098). Furthermore, we observed a statistically significant change of both MMT-12 (p=0, 017) and MMT-tight (p=0, 027). In addition we found a decrease of EAT score (p=0, 186), an improvement of pharyngeal muscle propulsion and a partial resolution of liquid stasis. Conclusions: According to literature, our findings indicate that Ig-iv therapy improves muscle weakness. Furthermore, a meaningful improvement of dysphagia also occurred, suggesting that Ig-iv may be considered an effective and safe treatment for refractory dysphagia in IIM patients. Further studies of larger cohort of patients are needed to confirm our results and evaluate the outcomes across time. References: Marie I et al. Intravenous immunoglobulins for steroid-refractory esophageal involvement related to polymyositis and dermatomyositis: a series of 73 patients. Arthritis Care Res (Hoboken). 2010 Dec;62(12):1748-55. Dalakas MC. The role of high-dose immune globulin intravenous in the treatment of dermatomyositis. Int Immunopharmacol. 2006 Apr;6(4):550-6. Epub 2005 Dec 20. Belafsky PC et al. Validity and reliability of the Eating Assessment Tool (EAT-10). Ann Otol Rhinol Laryngol. 2008 Dec;117(12):919-24. Schindler A. et al. Reliability and validity of the Italian Eating Assessment Tool. Ann Otol Rhinol Laryngol. 2013 Nov; 122(11):717-24. Katz U et al. Safety of intravenous immunoglobulin (IVIG) therapy. Autoimmun Rev. 2007 Mar;6(4):257-9. Epub 2006 Aug 28. Disclosure of Interest: None declared